Perceived Barriers and Facilitators of Return to Driving Among a Sample of Nigerian Stroke Survivors – A Qualitative Study (2021)
Stroke affects driving ability and as such impedes mobility, independence, freedom and quality of life. Return to driving after stroke serves as an integral part for community reintegration and improved quality of life. Driving is considered critical for continued independence, employment and recreation among stroke survivors. There was therefore the need to better understand the perceived facilitators and barriers to driving among stroke survivors with pre-stroke driving history. This study seeks to better understand the perceived facilitators of and barriers to return to driving after stroke so as to enable proper outcome in patient management and policy formulation. This is a qualitative phenomenological app roach using in-depth focus group discussion (FGD) was employed. Six stroke survivors (5 males; 1 female) aged 58.0 ± 7.9 years participated in the FGD. Half (50%) of the participants had returned to driving. Seven themes were generated for the barriers as well as facilitators of return to driving after stroke. Findings from this study suggests that majority of the facilitators of return to driving are intrinsic factors. Majority of stroke survivors wish that they could be able to stop being dependent on their caregivers for their activities of daily living (ADL) which could invariably lead to activity limitation and participation restriction. Attention should be paid on the pre-morbid driving status of stroke survivors so as to enhance the facilitators of return to driving and minimize the barriers to return to driving after stroke.